74. Mean glandular dose survey in the Emilia-Romagna region breast screening program. (December 2018) - Golinelli, P.; Acchiappati, D.; Angelini, L.; Berardi, P.; Bertolini, M.; Bianchini, D.; Cicoria, G.; Demetrio, D.; Fabbri, E.; Fabbri, S.; Farnedi, S.; Ghetti, C.; et al.
Abstract : Purpose: We have evaluated the Mean Glandular Doses (MGDs) of Full Field Digital Mammography (FFDM) systems, actually implemented in the Emilia Romagna Screening Program, using the same Plexiglas phantoms. This work aims to evidence the relevance of a large survey to estimate the variability of the doses provided by different mammographic systems available in this screening program. Methods: 75 FFDM systems, consisting of 1 Photon-Counting, 33 a-Se Direct, 30 CsI Indirect and 11 Computed Radiography (CR), were characterized by the average values of MGD (mGy) measurements of semi-circular phantom thicknesses of 20 mm, 45 mm and 60 mm. Images were acquired in automatic mode. MGDs were measured in accordance with the Mammo Protocol of the European Federation of Organisations for Medical Physics (EFOMP)[1] . Where available, Organ Doses (ODGs), calculated by manufacturers, were collected from the Header DICOM of the corresponding images and the differences with respect MGDs were evaluated. Results: All the MGDs values are within the EFOMP Mammo Protocol limits. Differences from MGDs and ODGs values are in between ±20% for the majority of systems, except for few ones. For 20 mm, 45 mm and 60 mm phantom thickness, the ranges of MGDs extend from 0.37 mGy to 1.00 mGy, 0.65 mGy to 2.40 mGy and from 1.33 mGy to 4.19 mGy respectively. As expected, MGDs show a strong dependence on FFDM system technology: the Photon Counting system has the lowest MGDs values, while the CR systems exhibit the highest ones. Conclusions: Our results confirm the importance of monitoring periodically the level of technology employed in a regional screening program by means of a dose survey, in order to promote a renewal of the FFDM imaging systems in accordance with the image quality preferences of the radiologists involved. This survey procedure would be functional also to guarantee the homogeneity of the Risk-Benefit Ratio.